Determinants of Nutritional Status Among Pregnant Women: a Transcultural Nursing Approach - Ni Ketut Alit Armini; Nurul Hidayati; Tiyas Kusumaningrum (Universitas Airlangga, 2020)
Introduction: Pregnant women experiencing poor nutritional status remains a problem which is still commonly found in Surabaya. Poor nutritional status is one of the causes of increased mortality in pregnant women. The mother's education and occupation, family income, number of children, and family shape are associated with the incidence of nutritional status in pregnant women. The purpose of this study was to explain the factors related to the nutritional status of pregnant women based on transcultural nursing theory. Methods: his study uses a cross-sectional design. The population were pregnant women at the Public Health Center Tanah Kali Kedinding Surabaya Indonesia, 104 respondents were selected using a consecutive sampling technique. The independent variables were technological, religious, family support, cultural values, political & legal, economic, and educational, while the dependent variable was the incidence of nutritional status in pregnant women. The data was obtained using questionnaires and mid upper arm circumstance (MUAC) measurements. The data was analyzed using the Spearman rho test. Results: There was a relationship between technological (p=0.001 ; r=0.332), family support (p=0.000 ; r=0.379), cultural values (p=0.000 ; r=0.702), political & legal (p=0.000 ; r=0.387), economic (p=0.031 ; r=0.212), and educational (p=0.020 ; r=0.228) factors with nutritional status in pregnant women. Discussion: Technological, family support, cultural values, political & legal, economic, and educational factors influenced the nutritional status of pregnant women. The cultural factor was the most dominant in influencing the nutritional status of pregnant women.